The Effect of Application of Learning Models Project Based Learning Canva’s Help to Increase Students’ Learning Creativity - Rini Supriani; Eko Priyanto; Efi Miftah Faridli (UM Purwokerto Press, 2024)
This research aims to find out whether there is an influence of implementing the learning model Project Based Learning assisted by Canva in increasing learning creativity on the material of the Unitary State of the Republic of Indonesia. The method used is quasi experiment with research design Nonequivalent Control Group Design. The sample in this research was class XI.6 students (n=36) as experimental class and students class XI.1 (n=36) as the control class. The data collection technique used in this research is an instrument in the form of a questionnaire/quesioner, tests, observations, and documentation studies. Analysis results with alternative tests paired sample test and independent sample t-test with results of 0.000 < 0.05, which means the learning model project based learning Canva's assistance influences students' learning creativity. From the percentage results, it can be seen that in the experimental class it was 73% while in the control class it was 69%. This shows that the application of the Project Based Learning learning model assisted by Canva has a significant effect on increasing the learning creativity of class XI students at SMA Negeri 2 Banjar.